Survey-studie på Hyllonox och Woodcoat - Broman, Anton; Johansson, Rasmus (2019)
The pine weeil (Hylobius abietis) is a beetle that eats bark on smaller plants, which can cause plants to die in the event of severe attacks. Without increased protection measures, up to 90 per cent of the plants are estimated to die in the pine weeil reared areas in southern and central Sweden.